Critical factors of the local firm industry and their implications. - Leong, Tina Yin Hwee. (2008)
This study is primarily a detailed analysis of 6 identified critical factors and their impact on Singaporean’s support for local films. Our research was motivated by the recent successes of 2 local movies, namely, “Money No Enough” and “Forever Fever”. For the purposes of our discussion, the following factors have been selected for our study: Film budget, the usage of Singlish, promotional efforts, governmental efforts, local identity markers and film ratings.